Early child care and the employment potential of mothers: Evidence from semi-parametric difference-in-differences estimation - Franziska Zimmert (Journal for Labour Market Research, 2023)
This paper examines the effect of an expansion of subsidized early child care on maternal labor market outcomes. It contributes to the literature by analyzing, apart from the employment rate, the adjustment of agreed working hours and especially of preferred working hours. Semi-parametric difference-in-differences estimation based on survey data from the German Microcensus results in positive effects on the employment rate, as well as on agreed and preferred working hours by up to 20% of the pre-reform mean. As agreed and preferred working hours adjust in line with each other, the expansion of early child care can tap labor market potentials beyond those of currently underemployed mothers. Moreover, conditional effects show that especially better educated and non-single mothers respond to the reform.
Keywords: J21; J22; I38; 330; Early child care; Maternal labor supply; Semi-parametric diference-in-diferences; Subsidized child care; Working hour preferences